2011
DOI: 10.1088/0953-8984/24/2/024207
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent dynamics of stochastic domain-wall depinning in nanowires

Abstract: The temperature dependence of domain-wall depinning in permalloy nanowires is investigated by measuring depinning fields and corresponding depinning times as a function of the external magnetic bias field. Domain walls are pinned at triangular notches in the nanowires and detected noninvasively by Hall micromagnetometry. This technique allows one to acquire depinning-field and depinning-time distributions in the temperature range between 5 and 50 K and thus to determine the stochastics of the depinning process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…This is of note because behaviours caused by conventional thermal activation typically take place on timescales much too long to be computationally accessible. Indeed, there is some evidence that thermally-activated transitions between DW states may also occur during DW depinning from notches 26 . Furthermore, other modelling 27 and experimental studies 28 have shown that DW pinning at small, roughness-related defect sites, can in-fact be a transient phenomena, with DWs thermally activating over energy barriers to continue their propagation.…”
Section: Discussionmentioning
confidence: 99%
“…This is of note because behaviours caused by conventional thermal activation typically take place on timescales much too long to be computationally accessible. Indeed, there is some evidence that thermally-activated transitions between DW states may also occur during DW depinning from notches 26 . Furthermore, other modelling 27 and experimental studies 28 have shown that DW pinning at small, roughness-related defect sites, can in-fact be a transient phenomena, with DWs thermally activating over energy barriers to continue their propagation.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of magnetic domain walls (DWs) driven by magnetic field [1][2][3][4][5][6][7][8][9][10][11] or electric current is often dictated by interactions with defects.…”
Section: Introductionmentioning
confidence: 99%
“…First, DW pinning and depinning has been widely observed to have stochastic character [20,21], a feature that would clearly disrupt the operation of gates. There are two possible causes of such behavior: Walker-breakdowninduced transformations of the DWs during propagation [22,23] and thermally induced effects once they are pinned [24]. In our simulations, we suppress Walker breakdown phenomena by using a high value of the Gilbert damping parameter (α ¼ 0.5).…”
Section: Discussionmentioning
confidence: 99%